Pyrolysis Behaviour of Muara Enim Coals: The Influence of Temperature and Ranks - Ulfa, Raden Maria; Esaki, Takehiro; Tambaria, Theodora Noely; Sugai, Yuichi (Geological Agency, 2026)
Underground coal gasification (UCG) is a clean coal technology that converts coal in-situ into synthetic gas (syngas) through thermal and chemical reactions. Coal pyrolysis, a key reaction in UCG, initiates the thermal decomposition of coal, and influences gas yield and composition. This study examines the influences of pyrolysis temperature and coal rank on gas production using coal samples from The Muara Enim Formation, South Sumatra Basin. Four coal samples, ranging from lignite to bituminous rank, were pyrolyzed at 300, 400, 500, and 600° C under inert conditions. The results indicate that gas yield increases with temperature due to enhanced thermal decomposition. At lower temperatures (300 ̶ 400° C) CO2 dominates, particularly in lower-rank coals due to their higher oxygen content. At higher temperatures (500 ̶ 600° C) more CH4 and H2 productions become more prominent, particularly in higher-rank coals. CH4 generation is driven by the breakdown of aliphatic structures, while H2 production results from dehydrogenation and condensation of aromatic structures. Lower-rank coal produced higher gas at low temperatures, indicating greater suitability for UCG under such conditions. In contrast, higher-rank coals require elevated temperatures for effective decomposition due to their greater thermal stability. These findings provide valuable geochemical insights into the pyrolysis behaviour of Muara Enim coals and offer a scientific basis for optimizing UCG conditions to improve gas yield and quality.